Sustainable Health and Wellbeing in the European Union - Beata Gavurova; Silvia Megyesiova (Frontiers Media S.A., 2022)
BackgroundAltogether, 17 Sustainable Development Goals (SDGs) are an urgent call for action to end poverty, protect the planet, and ensure prosperity for all. Goal 3 is crucial in terms of good health and wellbeing. The main aim of this study is to analyze and evaluate differences among indicators of SDG 3: Sustainable health and wellbeing in the EU countries.MethodsThe status and development of the EU Member States regarding their successes or failures in terms of Goal 3 were subjected to analysis. Altogether, 11 indicators were used to rank the EU countries using the TOPSIS and ranking methods. The ranks were assigned to the countries in two periods. The first period is related to the time from 2010 till 2014, and the second period from 2015 till 2019.ResultsThe EU countries achieved a positive development in 10 of 11 indicators that monitor the achievement of the EU in terms of Goal 3. The only variable that changed negatively was the obesity rate. Positivity was observed in the decline of the standardized preventable and treatable mortality, which declined from 317.3 in the first period to 295 in the second period; the drop of the population weighted annual mean concentration of fine particulate PM2.5, from 16.4 to 13.6 μg/m3, and also in the increase of the share of people with good or very good perceived health, which was combined with a decrease of the self-reported unmet need for medical examination and care. The best-rated country in terms of SDG 3 was, in both periods, Sweden, while the worst-rated was Latvia.ConclusionsGovernments and institutions in the EU can intervene to increase the accessibility and quality of the health care system, but every citizen should try to do their best to reduce some of the risk factors, such as smoking or obesity, to try living healthier and to help to achieve higher ambitions in terms of sustainable health and wellbeing.